Stage IV anal canal squamous cell carcinoma with long-term survival: a case report - Katsuji Sawai; Takanori Goi; Noriyuki Tagai; Hidetaka Kurebayashi; Mitsuhiro Morikawa; Kenji Koneri; Masato Tamaki; Makoto Murakami; Yasuo Hirono; Hiroyuki Maeda (Surgical Case Reports)
Abstract Background Currently, no established standard treatment exists for metastatic anal squamous cell carcinoma. We report a case of complete response in a patient with stage IV anal squamous cell carcinoma after undergoing multidisciplinary treatment. Case presentation A 62-year-old woman visited a nearby doctor with a chief concern of severe pain associated with a firm mass in the anus. The patient was diagnosed with anal canal squamous cell carcinoma and liver metastases and referred to First Department of Surgery Faculty of Medicine University of Fukui for treatment. The patient received a TNM classification of T4N0M1 and stage IV. Rectal amputation was performed; however, postoperative complications hindered immediate anticancer therapy and the liver metastases exacerbated. Radiofrequency hyperthermia and systemic chemotherapy were performed 3 months postoperatively. A prominent reduction in the liver metastasis was observed. Lung metastases appeared during the course of systemic chemotherapy. Radiotherapy was performed to treat the lung lesion and resolved. Radiotherapy was also performed for liver metastasis. The lesion in the liver showed resolution after 54 months postoperatively, and treatment with the anticancer drug was discontinued. Ten-year follow-up findings suggested complete resolution of the lesion in response to the treatment protocol followed in this case. This long-term survival was achieved through a multidisciplinary treatment. Conclusions The present case suggests that multidisciplinary treatment approach is effective for resolving stage IV anal squamous cell carcinoma, and addition of new anticancer drug therapy may improve the overall prognosis of squamous cell carcinoma.